Painting, photography and film in the work of Luigi Veronesi (L'uomo nero. Materiali per una storia delle arti della modernità, 2022)
Luigi Veronesi was a complex artist, with a wide variety of proposals, choices, and results. This complexity funded his activity from ‘20s to ‘90s, thus key point to understand his whole career, beyond of the verification of his own versatility. The essay proposed to analyze Veronesi’s artistic research – as painter, photographer, filmmaker, graphic designer, scenographer, costumer, designer of marionettes for theatre – from a point of view that aims to highlight his tension to complexity, differently from past lack of interest, misunderstanding, and negative judgment because of his non-academic approach and his Marxist and anti-idealist point of view.
Keywords: XX c. Italian Art; Luigi Veronesi